The Future of Moringa Foods: A Food Chemistry Perspective - Somoza, Veronika; Pirkwieser, Philip; Grosshagauer, Silke; Kraemer, Klaus (Frontiers in Nutrition, 2021)
The tree Moringa oleifera Lam. provides its leaves, pods, flowers and seeds for human nutrition. The chemical profile of all these Moringa products varies substantially, not only among the different parts of the plants used. Cultivating, processing as well as storage conditions chiefly determine the contents of nutrients and anti-nutritive constituents. Anti-nutrients, e.g., phytic acid or tannins, are present in notable amounts and may affect micronutrient bioavailability. Although Moringa oleifera products have been promoted for several health benefits and are discussed as an alternative treatment in various diseases, risk assessment studies evaluating contamination levels are scarce. Recent investigations have demonstrated alarming contents of heavy metals, polycyclic aromatic hydrocarbons and mycotoxins in Moringa oleifera products, indicating the need for a comprehensive risk assessment and contingent legal regulation of these products. In this mini review, we briefly outline pivotal, food chemistry and nutrition related data on Moringa preparations in order to stimulate in-depth research to close the presented knowledge gaps.